Synthesis and characterization of alkyl chain containing polytriazoleimide/reduced graphene oxide nanocomposites. Issue 12 (9th August 2017) - Balasubramanian, R.; Thirukumaran, P.; Parveen, A. Shakila; Babu, C.M.; Ramkumar, V.; Selvamani, A.; Srinivasan, V.V.; Lee, Jaewoong
Abstract : Polytriazoleimide/reduced graphene oxide (PTAI/RGO) nanocomposites were prepared by typical solution casting and thermal imidization method. Initially, the GO was synthesized by Hummers method, then reduced with hydrazine hydrate to obtain RGO and the diamine containing 1, 2, 3‐triazole ring and alkyl chain were synthesized by the 1, 3‐dipolar cycloaddition reaction in the presence of Cu(I) catalyst by click reaction. The monomers and polymers were characterized by FTIR and NMR spectroscopy. The mechanical, thermal, and morphological properties of PTAI/RGO (0, 1, 2 and 3 wt%) are reported. The glass transition temperature of the nanocomposites is in the range of 164–182°C. The tensile strength of the PTAI/RGO nanocomposites film was dramatically increased from 72 to 114 MPa from 0 to 3 wt% of RGO, which is ∼53% of improvement compared to that of pure PTAI films and the corresponding tensile modulus increased from 1.4 to 2.65 GPa. The thermogravimetric analysis (TGA) of the nanocomposites improved the thermal stability by the addition of RGO. The temperature corresponding 5% ( T 5% ) weight loss are in the range of 280–331°C. The dispersion of RGO in the surface of the nanocomposites was analyzed by scanning electron microscopy and transmission electron microscopy. This effective approach shows a potential application in polyimides‐based nanocomposites. POLYM. COMPOS., 39:4425–4433, 2018. © 2017 Society of Plastics Engineers